PENGARUH PERTAMBAHAN BERAT BADAN IBU SELAMA KEHAMILAN TERHADAP BERAT BADAN LAHIR BAYI, PANJANG BADAN BAYI, DAN LINGKAR KEPALA BAYI - , RIZKA DINARI; , dr. Detty Siti Nurdiati, MPH., PhD., Sp.OG(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Adequate gestational weight gain might be a prevention for unintended neonatal anthropometric outcome. Therefore, relationship between gestational weight gain and neonatal anthropometric outcome should be investigated. Goal: Examining relationship between gestational weight gain and birthweight, birth length, and head circumference at birth. Method: This cohort retrospective study involved 163 singleton pregnancy women delivered at RSKIA Sadewa, Yogyakarta in 2012. Total weight gain and weekly average weight gain were classified according IOM 2009. The relationship between each type of gestational weight gain and birth weight, birth length, and head circumference at birth was analyzed using chi-square test. Result: It was known that 42,9%, 31,5%, 25,6% of subjects were classified as normal, low, and high total weight gain, respectively. Besides, 34,5%, 16,7%, 61,9% of subjects were classified as normal, low, and high rate per week, respectively. Neonatal charactersitics were distributed to 1,8% low, 97,6% normal, and 0,6% high birth weight. In birth length category, 61,9%, 32,1%, 6,0% of neonates were classified as low, normal, and high, respectively. In head circumference at birth category, 41,7%, 48,8%, 9,5% of neonates were respectively classified as low, normal, high. After performing bivariate analysis, it was known that both total weight gain and weekly average weight gain were not associated with birth weight (p>0,05), birth length (p>0,05), and head circumference at birth (p>0,05). Conclusion: There is no association between gestational weight gain and birth weight, birth length, and head circumference at birth.